Pharmacokinetic Study of Anti-osteoarthritic Compounds of a Standardized Fraction from Sphaeralcea Angustifolia - Jade Serrano-Román; Pilar Nicasio-Torres; Elizabeth Hernández-Pérez; Enrique Jiménez-Ferrer (MDPI AG, 2021)
Sphaeralcea angustifolia has been widely used in inflammatory conditions such as blows, bruises, fractures, and wounds. The compounds identified as active in plants and suspension cell culture of S. angustifolia were tomentin, scopoletin, and sphaeralcic acid. To consolidate the integral use of knowledge about the S. angunstifolia and strengthen its pharmacological use in patients with knee osteoarthritis, the pharmacokinetic behavior of the active compounds was characterized. The SaTSS (S. angustifoloia standardized in Tomentin, Scopoletin, and Sphaeralcic acid) anti-ostearthritic fraction was obtained from cell suspension. The analytical method of High-Performance Liquid Chromatography (HPLC) for tomentin, scopoletin, and sphaeralcic acid were validated determining the accuracy, precision linearity, sensibility, specificity, detection limits, and quantification time-range parameters, as well as extraction efficiency and stability of compounds. The pharmacokinetic assay was performed with ICR mice strain, in which the mice were administrated with a single oral or intravenous dose (400 mg/kg with 7.1 mg/kg of scopoletin and tomentin in mixture and 34.6 mg/kg of sphaeralcic acid) of the SaTSS standardized active fraction. The results of the validated analytical methods allowed establishing, in a validated manner, that a coumarin mixture and sphaeralcic acid present in the SaTES fraction were detected in plasma. According to the values of Akaike Information Criteria (AIC), Sum of Squares (SS), Schwarz Criteria (SC), and by the determination coefficient (R2), the compounds follow a two-compartment model.